Analysis and Design of Recruitment Information System (Case Study: PT Bhumi Varta Technology) - Syafridamara, Muhammad Randa; Oetomo, Soegandi Sharma; Widjaya, Prya Artha (Formosa Journal of Applied Sciences, 2024)
The Recruitment Information System (RIS) is an information system designed to manage the recruitment process of new employees. The primary objective of RIS is to generate comprehensive human resource reports for stakeholders. This research was conducted in response to several issues faced by PT Bhumi Varta Technology, including poorly recorded recruitment processes, difficulties in managing recruitment records, and recruitment dynamics. The study focuses on analyzing and designing RIS for PT Bhumi Varta Technology, aiming to improve the recruitment process and assist stakeholders in decision-making. The outcome of this study is an RIS design that can be utilized by the company to meet its business needs. The RIS design involves various components such as rich pictures, use case diagrams, and user interfaces. The development of RIS adopts an object-oriented approach, incorporating activity diagrams and use case diagrams.